Isolation and Identification of Novel Non-Dairy Starter Culture Candidates from Plant Matrix Using Backslopping Propagation - Maret Andreson; Jekaterina Kazantseva; Aili Kallastu; Taaniel Jakobson; Inga Sarand; Mary-Liis Kütt (Fermentation)
The majority of non-dairy starter cultures on the market are originally isolated from milk and therefore do not provide the most optimal fermentation for plant matrices. Developing plant-derived starter cultures is essential for creating high-quality, tasty dairy alternatives. This study aims to isolate and characterize bacterial strains with the potential to be used as non-dairy starters from plant sources via backslopping evolution. A natural consortium of macerated plants was inoculated into two oat and two pea commercial drinks and backslopped for seventeen cycles to evolve the bacterial consortium at 25 °C, 34 °C, and 42 °C. The results showed that the initial natural consortium contained less than 1% lactic acid bacteria, and after the seventeenth cycle, lactic acid bacteria dominated in all investigated consortia. Oat Od1-25 and Od2-42 and pea Pd1-34 and Pd1-42 samples were selected for strain isolation based on amplicon-based metagenetic analysis of 16S rRNA gene sequencing and sensory properties. The strain isolation was performed using an out-plating technique, and colonies were identified by MALDI-TOF mass spectrometry. Altogether, eleven lactic acid bacteria species of plant origin were obtained. The strains belonged to the Leuconostoc, Enterococcus, Lactobacillus, and Lactococcus genera.